English file - Latham-Koenig, Christina. (Oxford University Press, 2014)
The English File Third Edition Teacher's Book offers a comprehensive walk-through guide to every lesson, in every unit of the English File Third Edition Student's Book, along with over 70 photocopiable activities. The English File Teacher's Book package comes complete with a Test & Assessment CD-ROM, which includes a complete test for every File, an End-of-course Test, two Progress Tests, and a Quick Test for every File.